The Effect of CoCoSo Method on the Ranks of Alternatives: A Case Study of Copper Electrical Wire Selection - Thinh, Hoang Xuan; Duc, Duong Van; Bao, Nguyen Chi (Engineering, Technology & Applied Science Research, 2024)
When using MCDM (Multi-Criteria Decision-Making) methods to rank alternatives, decision makers’ opinions have a huge influence on the ranking results. The decision makers’ opinions can vary depending on the chosen MCDM method, data normalization method, and weighting method. For some MCDM methods, during the application process, users also need to choose the value of a certain coefficient (called the user coefficient). Obviously, the value of the user coefficient depends on users’ opinions, and of course, these opinions can affect the ranking of the alternatives. In this article, the effects of users’ opinions on the ranks of the alternatives when using the CoCoSo (Combined Compromise Solution) method are investigated. Users’ opinions (including the weighting criteria method and the user coefficient) are considered the input of the investigation process. Organizing the investigation of the effects of these two parameters on the ranks of alternatives was applied to the case of copper electrical wire selection. The results show that the users’ opinions have little effect on the ranks of alternatives. This result confirms CoCoSo’s outstanding advantage.